DESCRIPTIVE ANALYSIS OF THE CURRENT STATE OF PUBLIC FINANCE MANAGEMENT OF UZBEKISTAN - Abdullayev Sukhrobiddin, Saidov Jasur (Journals Park Publishing, 2023)
This article examines public finance management, reforms implemented in Uzbekistan on effective public finance management, and priorities for improving the public finance system. The analysis of the research object has led to the conclusions that offers to develop mid-term budgeting, strategic approach in the current system of budget planning, increase the effectiveness of public procurement and investment management, develop a public debt management strategy, introduce an effective system of existing risk assessment to manage public assets and liabilities, to prevent irrational increase in budget obligations. In that way, the paper also discusses current issues of PFM in a broader sense. During the study, other works of local researchers on this topic were used to get additional insights that improve our descriptive research.
Keywords: PFM, GFS, strategy for optimizing public finance management, inter-budgetary transfers, government intervention, budget content.